Securing personal freedom through institutions – the role of electoral democracy and judicial independence - Niclas Berggren; Jerg Gutmann (University of Hamburg, Institute of Law and Economics (ILE), 2019)
Personal freedom is highly valued by many and a central element of liberal political philosophy. Although personal freedom is frequently associated with electoral democracy, developments in countries such as Hungary, Poland, Turkey and Russia, where elected populist leaders with authoritarian tendencies rule, suggest that electoral democracy may not be the envisaged unequivocal guarantor of freedom. Instead, an independent judicial system, insulated from everyday politics, might provide a firmer foundation. We investigate empirically how electoral democracy and judicial independence relate to personal freedom, as quantified by the new Human Freedom Index. Our findings reveal that while judicial independence is positively and robustly related to personal freedom in all its forms, electoral democracy displays a robust relationship with two out of seven types of personal freedom only (freedom of association, assembly and civil society as well as freedom of expression and information). These are types of freedom associated with democracy itself, but democracy seems unable to protect freedom in other dimensions. When we study interaction effects and make use of more refined indicators of the political system in place, we find that countries without elections or with only one political party benefit more from judicial independence than both democracies and multi-party systems without free elections. A number of robustness checks confirm these findings. Hence, it seems as if personal freedom has institutional correlates in the form of both democracy and judicial independence, with the latter safeguarding freedom more consistently and more strongly.
Keywords: D63; D72; D78; K36; K38; P48; 330; Freedom; democracy; judicial independence; political economy; institutions